Resilience and community pride after a hurricane: counter-narratives from rural water systems in Puerto Rico - Arce-Nazario, Javier A. (Alternautas, 2022)
When Hurricane María stripped Puerto Rico of its characteristic verdant foliage, it revealed complex layers of hidden geographies. The media coverage in the United States presented the destruction through visual and textual references to developing and “third-world” landscapes, while the accompanying headlines reminded us that its residents are “Americans”. This provocative juxtaposition was supported by several photographic themes, such as residents surveying debris or floods engulfing vehicles and neighborhoods. This article explores narratives of post-María experiences from non-PRASA communities. It is based on mixed-method interviews with non-PRASA community residents about conditions after the hurricane, in phone interviews conducted between September 2017 and January 2018, and in in-person interviews carried out in December 2017. Patterns are evident in these narratives that highlight the different experiences of consumers depending on their water source and access technology, and also highlight the contrasts that these residents drew with neighboring, PRASA-served communities. The experiences related below reveal how non-PRASA communities contribute to the overall Puerto Rican waterscape. They also illuminate issues around the discourses of sustainability and agency, development, society and technology, and colonialism.